2017
DOI: 10.1016/j.apsb.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Class I phosphatidylinositol 3-kinase inhibitors for cancer therapy

Abstract: The phosphatidylinositol 3-kinase (PI3K) pathway is frequently activated in human cancers. Class I PI3Ks are lipid kinases that phosphorylate phosphatidylinositol 4,5-bisphosphate (PIP2) at the 3-OH of the inositol ring to generate phosphatidylinositol 3,4,5-trisphosphate (PIP3), which in turn activates Akt and the downstream effectors like mammalian target of rapamycin (mTOR) to play key roles in carcinogenesis. Therefore, PI3K has become an important anticancer drug target, and currently there is very high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
92
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 101 publications
0
92
0
1
Order By: Relevance
“…The PI3K/AKT/mTOR pathway is frequently activated in cSCC, compared to actinic keratosis or normal skin (47). Class I PI3Ks phosphorylate phosphatidylinositol 4,5-bisphosphate (PIP2) at the 3-OH of the inositol ring to generate phosphatidylinositol 3,4,5-trisphosphate (PIP3), which in turn activates AKT and the downstream mTOR complex to play key roles in carcinogenesis (48). Activation of AKT will generate downstream effects, including the promotion of cell proliferation, migration and invasion, increasing cellular glycolytic flux and inhibiting cellular apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PI3K/AKT/mTOR pathway is frequently activated in cSCC, compared to actinic keratosis or normal skin (47). Class I PI3Ks phosphorylate phosphatidylinositol 4,5-bisphosphate (PIP2) at the 3-OH of the inositol ring to generate phosphatidylinositol 3,4,5-trisphosphate (PIP3), which in turn activates AKT and the downstream mTOR complex to play key roles in carcinogenesis (48). Activation of AKT will generate downstream effects, including the promotion of cell proliferation, migration and invasion, increasing cellular glycolytic flux and inhibiting cellular apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…6). As a result, inhibitors of PI3K/AKT/mTOR have been explored, among which a selective p110 inhibitor, idelalisib, in PIK3CA mutation-positive cancer has been approved for the treatment of chronic lymphocytic leukemia (CLL) and follicular B-cell lymphoma of non-Hodgkin's lymphoma (48). However, no clinical studies have reported the role of PI3K/AKT pathway-targeting drugs in cSCC to date.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of this enzyme showed potent anticancer activity, but until now all the reported PI 3 K inhibitors such as GDC‐0941 or pictilisib ( 57 ) showed elevated resistance rates render its use as single agent is not suitable for combating cancer. As a result, it is used in combination with other pathways inhibitors to target multiple pathways . On the other hand, it was found that the combination index between pictilisib ( 57 ) and the HDAC inhibitor SAHA is less than one proving their synergism .…”
Section: Design Of Dual Pi3k/hdac Inhibitorsmentioning
confidence: 99%
“…As a result, it is used in combination with other pathways inhibitors to target multiple pathways. 65 On the other hand, it was found that the combination index between pictilisib (57) and the HDAC inhibitor SAHA is less than one proving their synergism. 66 As a result, Qian et al 66 developed the first chimeric HDAC /PI 3 K inhibitor hybrid 58 or called CUDC-907 ( Figure 17).…”
Section: Design Of Dual C-met/hdac Inhibitorsmentioning
confidence: 99%
“…While PI3Kd and PI3Kg are well known to be involved in the immune system and inflammation (15,16), PI3Kd-specific inhibitors have demonstrated antitumor effects. In particular, idelalisib (CAL101) has become the first approved PI3K inhibitor for treatment of patients with relapsed chronic lymphocytic leukemia (17). We previously reported that the pan-PI3K inhibitor ZSTK474 exhibited antimetastatic effects via blocking migration and suppressing matrix metalloproteinase secretion of prostate cancer PC3 cells (18).…”
mentioning
confidence: 99%